Implementasi Layanan Informasi dalam Menanggulangi Tindakan Cyberbullying di SMA Swasta Al–Maksum Desa Cinta Rakyat Kecamatan Percut Sei Tuan - Almadani, Nur Muhammad Ridho (Al-DYAS, 2023)
This study entitled "Implementation of Information Services in Dealing with Cyberbullying in Al-Maksum Private High School Cinta Rakyat Village, Percut Sei Tuan District" which aims to find out: (1) The role of the Counseling Teacher in providing information services in tackling cyberbullying in Al-Maksum Private High School Percut Sei Tuan District (2) The impact caused by cyberbullying which resulted in the physical and psychological conditions of students at school. The method used in this study is a qualitative method, research data collection is carried out by utilizing observation, interviews and documentation studies. The findings of this study reveal two findings, namely: (1) Counseling teachers play an important role in implementing information services in schools, one of which is providing direction and information knowledge about cyberbullying. Counseling teachers provide services in the form of information to Al-Masum Private High School students about understanding the effects of cyberbullying on changes in behavior caused to people subjected to cyberbullying. (2) The impact of changes in students' social behavior. Changes occur significantly. Because there are some students who experience changes in their social behavior, namely after the cyberbullying action occurs it causes a student to want to quit school and the student's level of self-confidence decreases.